Altonaischer Gelehrter Mercurius vols. 1-7 (Altona Burmester, 1763)
This newspaper, which for 24 volumes appeared on a weekly basis, was renamed 'Neuer gelehrter Mercurius' in 1773, 'Neuester Altonaischer gelehrter Mercurius' in 1787. It is one of the most important learned and critical journals of the eighteenth century. In addition to reviews of newly published 'learned writings', it also offers 'notes' and news from the republic of letters.
Altona is the westernmost urban borough of the German city state of Hamburg, on the right bank of the Elbe river. From 1640 to 1864, Altona was under the administration of the Danish monarchy. It became part of the Kingdom of Prussia in 1867. In 1938, the Greater Hamburg Act removed Altona from the Free State of Prussia and merged it with the Free and Hanseatic City of Hamburg.
All volumes have uncut pages
Ex libris Bibliotheca Krassow (stamp)
Vols. 1-6 are paper-bound, vol. 7 has a modern marbled cardboard binding with leather spine
Keywords: 18th Century (1701-1800); History; Journalism; Music criticism; Natural science; Abendmusiken; akoestiek; Algarotti; Algarotti; Bach, C.P.E.; bibliotheek; bibliotheek; bibliotheek; bibliotheek; bibliotheek; bibliotheek; bibliotheek; bier; blaasinstrumenten_ziektes; Blainville; boekoplage; Batteux; Batteux; Boerhave; Boerhave; Boileau; beiaard / klokken; Borde, de la; Bos, Abbé du; Bossuet; Bossuet, J.B.; Brockes; Brosses, de; Burmann, P; calcant (orgelcalcant); muziek_algemeen; muziek_algemeen; muziek_algemeen; muziek_algemeen; muziek_algemeen; Christina van Zweden; Christine van Zweden; Nederlandse geleerden; Newton; Newton; Newton; Corneille, P; Corneille, P; Corneille, P; orgelbouw; dansen; dansen; oud-nieuw; Destouches; Diderot & D'Alembert_Encyclopedie; Dijk, van; doedelzak; Pascal, B; Pepys; pest